SEVOFLURANLA TEK SOLUK İNDÜKSİYONU İLE PROPOFOL İNDÜKSİYONUNUN ENTÜBASYONA HEMODİNAMİK YANITLARININ KARŞILAŞTIRILMASI - EKİCİ, Birsel; KARACA, Saffet; SALİHOĞLU, Ziya; DEMİROLUK, İ. Şener; KÖSE, Yıldız (Cerrahpaşa Medical Journal, 2019)
Background and Design.- In this study we aimed to compare single breath with sevoflurane and propofol intravenous induction for responses to tracheal intubation. ASA I-II groups 40 patients were included in this study. They were randomly allocated into two groups as sevoflurane (n=20) and propofol groups (n=20). As premedication, 1,5 mg/kg fentanyl was administered intravenously. Patients were breathed 100 % oxygen during 2 minutes period. In the sevoflurane group, 8 % vol sevorane, 33 % oxygen 67 % N2O mixture was breathed with single breath technique. When cornea reflex disappeared, sevorane concentration decreased 3 % of the volume. In propofol group, 2 mg/ kg propofol was administered intravenously. Patients were breathed 33 % oxygen 67 % N2O mixture. After 0,1 mg/kg vecuronium administration, endotracheal entubation was performed. Mean arterial pressure, heart rate and oxygen saturation values was enrolled. Results.- There were no difference with all measuring parameters. Only in the propofol group there was significantly decrease in MAP at the first minute (p<0.05). Conclusion.- As a conclusion hemodynamic parameters in the sevuflurane group was influenced lower than the propofol group.